Discursive Features Of Conditionals In English And Uzbek Literature (Texas Journal of Multidisciplinary Studies, 2026)
This article analyzes the discursive features of conditionals in English and Uzbek literature. It examines the functional role, stylistic potential, and pragmatic significance of conditional constructions within literary texts from a comparative perspective. The study demonstrates that conditionals function not only as grammatical structures but also as important discursive devices that contribute to meaning construction and authorial intention in literary discourse.